Review paperCutaneous adverse effects of nonsteroidal anti-inflammatory drugs - Broniarczyk-Dyła, Grażyna; Urysiak-Czubatka, Izabela (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2007)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are the most frequently prescribed drugs. Most of them are widely available and purchased without prescription. NSAIDs are used not only for their antipyretic, but also analgesic and anti-inflammatory effects. They are used very often in various chronic diseases. Increased incidence of adverse effects after these drugs is connected with the lack of good information for patients about the risks of taking NSAIDs for a long time, polypragmasy and wide media advertising. The fact that various drugs often provoke similar skin lesions and even the same drug can provoke different morphological reactions makes the diagnostic process of the described dermatoses very difficult. Nonsteroidal anti-inflammatory drugs, similarly to radiological contrast medium, mannitol, dextran or topical anaesthetic agents, provoke reactions clinically suggesting allergic reactions. However, they do not involve immunoglobulins E (IgE). These are non-allergic hypersensitivity reactions, also called intolerance reactions, pseudoallergies or idiosyncrasies. The skin is a place where drugs are metabolized extrahepatically. Because of this fact skin is especially prone to hypersensitivity reactions. Urticaria, angioedema, erythemas, exanthematous drug eruptions, purpura and phototoxic reactions are the most common cutaneous changes after taking NSAIDs.